Nation of victims : identity politics, the death of merit, and the path back to excellence - Ramaswamy, Vivek (Center Street, 2022)
"The New York Times bestselling author of Woke Inc. makes the case that the essence of true American identity is to pursue excellence unapologetically and reject victimhood culture." -- Amazon.com.